Thiolate-capped CdSe/ZnS core-shell quantum dots for the sensitive detection of glucose - Rahman, Samsulida Abd.; Ariffin, Nurhayati; Yusof, Nor Azah; Abdullah, Jaafar; Mohammad, Faruq; Zubir, Zuhana Ahmad; Aziz, Nik Mohd Azmi Nik Abd. (MDPI, 2017)
A semiconducting water-soluble core-shell quantum dots (QDs) system capped with thiolated ligand was used in this study for the sensitive detection of glucose in aqueous samples. The QDs selected are of CdSe-coated ZnS and were prepared in house based on a hot injection technique. The formation of ZnS shell at the outer surface of CdSe core was made via a specific process namely, SILAR (successive ionic layer adsorption and reaction). The distribution, morphology, and optical characteristics of the prepared core-shell QDs were assessed by transmission electron microscopy (TEM) and spectrofluorescence, respectively. From the analysis, the results show that the mean particle size of prepared QDs is in the range of 10–12 nm and that the optimum emission condition was displayed at 620 nm. Further, the prepared CdSe/ZnS core shell QDs were modified by means of a room temperature ligand-exchange method that involves six organic ligands, L-cysteine, L-histidine, thio-glycolic acid (TGA or mercapto-acetic acid, MAA), mercapto-propionic acid (MPA), mercapto-succinic acid (MSA), and mercapto-undecanoic acid (MUA). This process was chosen in order to maintain a very dense water solubilizing environment around the QDs surface. From the analysis, the results show that the CdSe/ZnS capped with TGA (CdSe/ZnS-TGA) exhibited the strongest fluorescence emission as compared to others; hence, it was tested further for the glucose detection after their treatment with glucose oxidase (GOx) and horseradish peroxidase (HRP) enzymes. Here in this study, the glucose detection is based on the fluorescence quenching effect of the QDs, which is correlated to the oxidative reactions occurred between the conjugated enzymes and glucose. From the analysis of results, it can be inferred that the resultant GOx:HRP/CdSe/ZnS-TGA QDs system can be a suitable platform for the fluorescence-based determination of glucose in the real samples.